Bioimpedance Phase Angle as a Prognostic Tool in Late-Onset Pompe Disease: A Single-Centre Prospective Study With a 15-year Follow-Up - Ravaglia, Sabrina; de Giuseppe, Rachele; Carlucci, Annalisa; Jehne, Susan; Crescimanno, Grazia; Ahmad, Lara; Paoletti, Matteo; Clemente, Gabriele; Pichiecchio, Anna; Bazzano, Rosella; Cirio, Serena; Valente, Enza Maria; et al. (Frontiers in Cell and Developmental Biology, 2022)
Background: Late-onset Pompe disease is an autosomal-recessive metabolic myopathy caused by deficiency of the lysosomal enzyme Acid Alpha – Glucosidase (GAA), leading to glycogen accumulation in proximal and axial muscles, and in the diaphragm. Enzyme Replacement Therapy with recombinant GAA became available in 2006. Since then, several outcome measures have been investigated for the adequate follow-up of disease progression and treatment response, usually focusing on respiratory and motor function. Methods: In this single Centre, prospective study, we evaluate the response to enzyme replacement therapy in 15 patients (7 males) with LOPD in different stages of disease, aged 49.4+16.1, followed-up for 15 years. Treatment response was measured by the six-minute walking test, vital capacity in supine and upright position, respiratory muscle strength, muscle MRI, manual muscle testing. We investigated the usefulness of Body Impedance Vectorial Analysis for serial body composition assessment. Results: Although monst patients with LOPD benefit from long-term treatment, some secondary decline may occur after the first 3-5 years. Some nutritional (lower body mass index, higher fat free mass, higher phase angle) and disease parameters (higher creatine-kinase levels and shorter disease duration at the beginning of treatment) seem to predict a better motor outcome. Lower Phase Angle correlates with worse treatment response on long-term follow-up. Conclusions: Body Impedance Vectorial Analysis is a fast, easily performed and cheap tool that may be able to predict long-term treatment response in patients with LOPD. Low Phase angle may help to identify those patients who need a closer follow-up due to higher fragility and risk of deterioration.